RELIGION AND LANGUAGE - Aykara, Thomas (Journal of Dharma, 1992)
Religion and language are two fundamental dimensions of man, two profound directions of his being, two essential expressions of his inner directedness and existential embodiment. Quest is at the heart of both. As the quest gets stifled, religion starts dying. While religion is an attitude welling up from the very core of his being, language is the articulation of the quest of the being. Language, said Martin Heidegger, is the "house of being.' Both religion and language are embedded in the very being of man. The Greeks defined him Zoon logon echon- 'the living being that has the word'; contemporary existentialist philosophers will say that he is a speaking word; a word spoken, a word having and giving a wealth of meanings and values.